HUBUNGAN KADAR HbA1C DENGAN GANGGUAN PENDENGARAN SENSORINEURAL PADA PASIEN DM TIPE 2 - NANTIKA SITOMPUL, ASMA DWI; NASUTION, MUHAMMAD EDY SYAHPUTRA (LP2MTBM MAKARIOZ, 2023)
Diabetes Mellitus (DM) is a metabolic disease with characteristics of hyperglycemia and one of the complications that can be caused by DM is hearing loss, especially sensorineural deafness. In type 2 DM patients whose HbA1c is not controlled will experience hearing loss in which DM it self will damage the auditory nerve which is commonly referred to as auditory nerve neuropathy. The purpose of the study was to determine the relationship between HbA1c and sensorineural hearing loss in type 2 DM patients. This study was an analytical study with a cross-sectional approach to 40 type 2 DM patients aged 40-65 years at Iman Martubung Clinic. Based the result are the most samples were women aged 51-60 years (62.5%). The results of the examination were dominated by HbA1C 6.5% and had sensorineural hearing loss as many as 28 people (87.5%) and the relationship between HbA1C and sensorineural hearing loss in type 2 DM patients with analytical techniques using Fisher's exact test with a value (p = 0.008) showed significant results between HbA1c and sensorineural hearing loss in type 2 DM patients. In this study, there was a connection between HbA1C and sensorineural hearing loss in type 2 DM patients.